Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Describe and correct the error in finding the difference of the polynomials
(4x2 – x+3) – (3x2 - 5x - 6) = 4x2 – x+3 – 3x2 – 5x – 6
= 4x2 – 3x2 - x = 5x +3 - 6
=x² - 6x-3


Sagot :

Answer:

4x+11 is the answer.

Step-by-step explanation:

( 4*2-x+3)-(3*2-5x-6)

=(8-x+3)-(6-5x-6)

=(11-x)-(0-5x)

=(11-x)-(-5x)

=11-x+5x

=11+4x

= 4x+11